Evaluation of high‐intensity focused ultrasound ablation for uterine fibroids: an IDEAL prospective exploration study. (5th June 2017) - Chen, J; Li, Y; Wang, Z; McCulloch, P; Hu, L; Chen, W; Liu, G; Li, J; Lang, J; ,
Abstract : Objective: To evaluate the clinical outcomes of high‐intensity focused ultrasound (HIFU) and surgery in treating uterine fibroids, and prepare for a definitive randomised trial. Design: Prospective multicentre patient choice cohort study (IDEAL Exploratory study) of HIFU, myomectomy or hysterectomy for treating symptomatic uterine fibroids. Setting: 20 Chinese hospitals. Population or sample: 2411 Chinese women with symptomatic fibroids. Methods: Prospective non‐randomised cohort study with learning curve analysis (IDEAL Stage 2b Prospective Exploration Study). Main outcome measures: Complications, hospital stay, return to normal activities, and quality of life (measured with UFS‐Qol and SF‐36 at baseline, 6 and 12 months), and need for further treatment. Quality‐of‐life outcomes were adjusted using regression modelling. HIFU treatment quality was evaluated using LC‐CUSUM to identify operator learning curves. A health economic analysis of costs was performed. Results: 1353 women received HIFU, 472 hysterectomy and 586 myomectomy. HIFU patients were significantly younger ( P < 0.001), slimmer ( P < 0.001), better educated ( P < 0.001), and wealthier ( P = 0.002) than surgery patients. Both UFS and QoL improved more rapidly after HIFU than after surgery ( P = 0.002 and P = 0.001, respectively at 6 months), but absolute differences were small. Major adverse events occurred in 3 (0.2%) of HIFU and in 133 (12.6%) of surgical cases ( P < 0.001). Median time for hospital stay was 4 days (interquartile range, 0–5 days), 10 days (interquartile range, 8–12.5 days) and 8 days (interquartile range, 7–10 days). Conclusions: HIFU caused substantially less morbidity than surgery, with similar longer‐term QoL. Despite group baseline differences and lack of blinding, these findings support the need for a randomised controlled trial (RCT) of HIFU treatment for fibroids. The IDEAL Exploratory design facilitated RCT protocol development. Tweetable abstract: HIFU had much better short‐term outcomes than surgery for fibroids in 2411‐patient Chinese IDEAL format study. Tweetable abstract: HIFU had much better short‐term outcomes than surgery for fibroids in 2500‐patient Chinese IDEAL format study.